Artificial intelligence and literacy. Promoting a human-centric sociological approach to overcome prejudice and foster social inclusion - Boriati, Danilo; D’Ambrosio, Mariangela (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Starting from a sociological analysis of the role of artificial intelligence in contemporary society, the essay focuses on digital literacy as the ability to use digital technologies efficiently and critically, in a way that promotes a conscious use of technologies and puts humans at the centre as agents endowed with consciousness, evaluation, and interpretation.